Exchange Rate Co-movements and Business Cycle Synchronization between Japan and Korea - Sammo Kang; Yunjong Wang; Deok Ryong Yoon (Asian Development Bank Institute (ADBI), 2002)
Japan and the Republic of Korea (Korea) are close countries in terms of economic interaction and geography and important to the economic growth and development of the region. To quantify the impact of changes in the yen/dollar exchange rate and Japanese industrial production on the Korean economy before and after the East Asian financial crisis of 1997, the sample period is divided into two sub-periods and then the causal relationships are examined by using vector auto-regression analysis. Our estimates show that while the response of Korean industrial production to changes in the yen/dollar exchange rate is not significant during the pre-crisis period, it becomes significant during the post-crisis period. The forecast error variance decomposition also confirms that yen/dollar exchange rate shocks have almost negligible explanatory power with regards to Korean industrial production during the pre-crisis period, but they have some significance for the post-crisis period. These empirical results show that the free floating exchange rate regime adopted by Korea since the crisis cannot insulate its economy from external nominal shocks such as yen/dollar exchange rate volatility.
hdl:11540/4146
Keywords: 330